2018
DOI: 10.18261/issn.1891-943x-2018-01-04
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Participants’ Experiences fromthe First International MOOC Offered at the University of Oslo

Abstract: This paper explores pedagogical practices and participants' engagement in learning activities during the first international Massive Open Online Course (MOOC) offered by the University of Oslo through the FutureLearn platform in 2015. The data were collected using pre-and post-course surveys and participant observations. We used the acquisition and participation metaphors of learning proposed by Sfard (1998) as a conceptual framework to inform our analyses and discussions. The data indicated that new pedagogic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 41 publications
0
25
0
2
Order By: Relevance
“…Kim et al (2014) identified five student interaction patterns with videos: starting from the beginning of new material; returning to missed content; following a tutorial step; replaying a brief segment; and repeating a non-visual explanation. Videos can also provide a valuable context for learning and generate a common experience for students to discuss and reflect on concepts and ideas, as in anchored instruction (Bonk, 2011;Langset et al, 2018;Sherer and Shea, 2011;Singh and Mørch, 2018). By generating a common experience for learners, videos can enhance students' engagement in collaborative activities and promote different learning styles (Calandra et al, 2006;Goulah, 2007;Greenberg and Zanetis, 2012;Pea and Lindgren, 2008;Zhang et al, 2006).…”
Section: Video Resources In Online Courses and Moocsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kim et al (2014) identified five student interaction patterns with videos: starting from the beginning of new material; returning to missed content; following a tutorial step; replaying a brief segment; and repeating a non-visual explanation. Videos can also provide a valuable context for learning and generate a common experience for students to discuss and reflect on concepts and ideas, as in anchored instruction (Bonk, 2011;Langset et al, 2018;Sherer and Shea, 2011;Singh and Mørch, 2018). By generating a common experience for learners, videos can enhance students' engagement in collaborative activities and promote different learning styles (Calandra et al, 2006;Goulah, 2007;Greenberg and Zanetis, 2012;Pea and Lindgren, 2008;Zhang et al, 2006).…”
Section: Video Resources In Online Courses and Moocsmentioning
confidence: 99%
“…The ICTMOOC has the structure of an xMOOC, it is built in the Canvas platform and is aimed to enhance the development of digital skills with pre-and in-service teachers. Researchers define xMOOCs as courses that are institutionally focused, reliant on video lectures and provide automated assessment through quizzes (Bayne and Ross, 2014;Singh and Mørch, 2018), and all of these elements are present in the ICTMOOC. The ICTMOOC consists of 10 modules to be completed by the participants progressively over the course of 10 weeks.…”
Section: Ictmoocmentioning
confidence: 99%
See 1 more Smart Citation
“…La première catégorie est d'ordre théorique, elle vise à cerner les causes du manque de motivations (Alario-Hoyos et al, 2017 ;Bakki et al, 2015 ;Hew & Cheung, 2014a ;Howarth et al, 2016 ;Watted & Barak, 2018 ;Zheng et al, 2016) et d'engagement des apprenants dans ces environnements (Bonafini et al, 2017 ;Milligan et al, 2013 ;Singh & Mørch, 2018).…”
Section: Dropout Et Taux De Rétention Dans Les Moocunclassified
“…Other papers addressed users' perspectives. For example, Singh and Mørch (2018) shed light on participants' experiences and pedagogical design, whereas Jacobsen (2019) explored participants' motivations and learning strategies. Three papers addressed the role of MOOCs from organisational perspectives, including how they might act as strategic means for continuing professional education purposes (Koch, 2017;Langseth et al, 2018Langseth et al, , 2019Haugsbakken et al, 2019;Tømte, 2019) and how the conceptualisations of MOOCs as educational offerings challenge existing organisational structures (Tømte, 2019).…”
Section: Norwaymentioning
confidence: 99%